Peningkatan Kinerja Organisasi Melalui Perencanaan Strategi - Widodo Widodo (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2011)
AbstractThe purpose of this study was to test empirically the effects of cross-functional integration, communication quality, completeness, commitment, capability, content strategy and organizational performance adaptability. With purposive sampling, respondents to this study is 120 executives from a total of 526 executives of small banks in the Province of Central Java. The data were analyzed using SEM (Structural Equation Model) with the AMOS program. The findings of this study indicate that all hypotheses have been significantly accepted. Thus, the managerial implications of these findings as an effort to improve the quality of organizational performance can be achieved through improving the quality of service content strategy that is built with highly adaptabilityKeywords: organizational performance, communication quality, completeness, commitment, capability, content strategy. AbstrakTujuan penelitian ini adalah untuk menguji secara empiris efek lintas-fungsional integrasi, kualitas komunikasi, kelengkapan, komitmen, kemampuan, strategi konten dan kemampuan beradaptasi kinerja organisasi. Dengan metode purposive sampling, responden untuk penelitian ini adalah 120 eksekutif dari total 526 eksekutif perbankan kecil di Propinsi Jawa Tengah. Data kemudian dianalisis dengan menggunakan SEM (Structural Equation Model) dengan program AMOS. Temuan penelitian ini menunjukkan bahwa semua hipotesis yang dibangun dapat diterima secara significan. Implikasi manajerial dari temuan ini sebagai upaya meningkatkan kualitas kinerja organisasi dapat di capai melalui meningkatan kualitas pelayanan strategi konten yang dibangun dengan kemampuan adaptasi yang tinggi.Kata kunci: kinerja organisasi, kualitas komunikasi, kelengkapan, komitmen, kemampuan, strategi konten